Gold-Catalyzed Homogeneous (Cyclo)Isomerization Reactions - Marín-Luna, Marta; Nieto Faza, Olalla; Silva López, Carlos (Frontiers in Chemistry, 2019)
Gold is currently one of the most used metals in organometallic catalysis. The ability of gold to activate unsaturated groups in different modes, together with its tolerance to a wide range of functional groups and reaction conditions, turns gold-based complexes into efficient and highly sought after catalysts. Natural products and relevant compounds with biological and pharmaceutical activity are often characterized by complex molecular structures. (Cyclo)isomerization reactions are often a useful strategy for the generation of this molecular complexity from synthetically accesible reactants. In this review, we collect the most recent contributions in which gold(I)- and/or gold(III)-catalysts mediate intramolecular (cyclo)isomerization transformations of unsaturated species, which commonly feature allene or alkyne motifs, and organize them depending on the substrate and the reaction type.